Effects of Guideline and Formulary Changes on Statin Prescribing in the Veterans Affairs. (12th November 2017) - Markovitz, Adam A.; Holleman, Rob G.; Hofer, Timothy P.; Kerr, Eve A.; Klamerus, Mandi L.; Sussman, Jeremy B.
Abstract : Objective: To compare the effects of two sequential policy changes—the addition of a high‐potency statin to the Department of Veterans Affairs (VA) formulary and the release of the American College of Cardiology/American Heart Association (ACC/AHA) cholesterol guidelines—on VA provider prescribing. Data Sources/Study Setting: Retrospective analysis of 1, 100, 682 VA patients, 2011–2016. Study Design: Interrupted time‐series analysis of changes in prescribing of moderate‐to‐high‐intensity statins among high‐risk patients and across high‐risk subgroups. We also assessed changes in prescribing of atorvastatin and other statin drugs. We estimated marginal effects (ME) of formulary and guideline changes by comparing predicted and observed statin use. Data Collection/Extraction Methods: Data from VA Corporate Data Warehouse. Principal Findings: The use of moderate‐to‐high‐intensity statins increased by 2 percentage points following the formulary change (ME, 2.4, 95% confidence interval [CI], 2.2 to 2.6) and less than 1 percentage point following the guideline change (ME, 0.8, 95% CI, 0.6 to 0.9). The formulary change led to approximately a 12 percentage‐point increase in the use of moderate‐to‐high‐intensity atorvastatin (ME, 11.5, 95% CI, 11.3 to 11.6). The relatively greater provider response to the formulary change occurred across all patient subgroups. Conclusions: Addition of a high‐potency statin to formulary affected provider prescribing more than the ACC/AHA guidelines.